Evolution of interference competition by individual, family, and group selection - Wade, Michael J. (1982)
The necessary conditions for the evolution of social behaviors in a population with three levels of biological organization are derived by using a population genetic model (one locus, two alleles, random mating, discrete generations). Total selection on the behavior, Δq, is partitioned into the sum of three components: (i) Δq(I), selection between individuals within families; (ii) Δq(F), selection between families within groups; and (iii) Δq(G), selection between groups of families. I show that any level of selection can be made to operate in concert with or in opposition to any other, depending upon the fitness effects of the behavior. The implications of the model are discussed in relation to those adaptive explanations of phenotypic traits that generally consider selection to operate only between individuals.